Rationale, Design, and Baseline Characteristics of the CURRENT AS Registry-2 - Watanabe, Hirotoshi; Miyake, Makoto; Ishii, Mitsuru; Takeji, Yasuaki; Morimoto, Takeshi; Tsuneyoshi, Hiroshi; Murai, Ryosuke; Nakayama, Hiroyuki; Nakatsuma, Kenji; Murata, Koichiro; Osakada, Kohei; Shirai, Shinichi; et al. (Circulation Journal, 2022)
Background: There is scarce data evaluating the current practice pattern and clinical outcomes for patients with severe aortic stenosis (AS), including both those who underwent surgical aortic valve replacement (SAVR) or transcatheter aortic valve implantation (TAVI) and those who were managed conservatively in the TAVI era.Methods and Results: The Contemporary outcomes after sURgery and medical tREatmeNT in patients with severe Aortic Stenosis (CURRENT AS) Registry-2 is a prospective, physician-initiated, multicenter registry enrolling consecutive patients who were diagnosed with severe AS between April 2018 and December 2020 among 21 centers in Japan. The rationale for the prospective enrollment was to standardize the assessment of symptomatic status, echocardiographic evaluation, and other recommended diagnostic examinations such as computed tomography and measurement of B-type natriuretic peptide. Moreover, the schedule of clinical and echocardiographic follow up was prospectively defined and strongly recommended for patients who were managed conservatively. The entire study population consisted of 3,394 patients (mean age: 81.6 years and women: 60%). Etiology of AS was degenerative in 90% of patients. AS-related symptoms were present in 60% of patients; these were most often heart failure symptoms. The prevalence of high- and low-gradient AS was 58% and 42%, respectively, with classical and paradoxical low-flow low-gradient AS in 4.6% and 6.7%, respectively.Conclusions: The CURRENT AS Registry-2 might be large and meticulous enough to determine the appropriate timing of intervention for patients with severe AS in contemporary clinical practice.